Hydrogen Sulfide and Polysulfides as Biological Mediators - Hideo Kimura (Molecules, 2014)
Hydrogen sulfide (H2S) is recognized as a biological mediator with various roles such as neuromodulation, regulation of the vascular tone, cytoprotection, anti-inflammation, oxygen sensing, angiogenesis, and generation of mitochondrial energy. It is produced by cystathionine β-synthase (CBS), cystathionine γ-lyase (CSE), and 3-mercaptopyruvate sulfurtransferase (3MST). The activity of CBS is enhanced by S-adenosyl methionine (SAM) and glutathionylation, while it is inhibited by nitric oxide (NO) and carbon monoxide (CO). The activity of CSE and cysteine aminotransferase (CAT), which produces the 3MST substrate 3-mercaptopyruvate (3MP), is regulated by Ca2+. H2S is oxidized to thiosulfate in mitochondria through the sequential action of sulfide quinone oxidoreductase (SQR), sulfur dioxygenase, and rhodanese. The rates of the production and clearance of H2S determine its cellular concentration. Polysulfides (H2Sn) have been found to occur in the brain and activate transient receptor potential ankyrin 1 (TRPA1) channels, facilitate the translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) to the nucleus, and suppress the activity of phosphatase and tensin homolog (PTEN) by sulfurating (sulfhydrating) the target cysteine residues. A cross talk between H2S and NO also plays an important role in cardioprotection as well as regulation of the vascular tone. H2S, polysulfides, and their cross talk with NO may mediate various physiological and pathophysiological responses.